A Precision Medicine Guided Approach to the Utilization of Biomarkers in MASLD - Thakral, Nimish; Desalegn, Hailemichael; Diaz, Luis Antonio; Cabrera, Daniel; Loomba, Rohit; Arrese, Marco; Arab, Juan Pablo (Seminars in Liver Disease, 2024)
The new nomenclature of metabolic dysfunction-associated steatotic liver disease (MASLD) emphasizes a positive diagnosis based on cardiometabolic risk factors. This definition is not only less stigmatizing but also allows for subclassification and stratification, thereby addressing the heterogeneity of what was historically referred to as nonalcoholic fatty liver disease. The heterogeneity within this spectrum is influenced by several factors which include but are not limited to demographic/dietary factors, the amount of alcohol use and drinking patterns, metabolic status, gut microbiome, genetic predisposition together with epigenetic factors. The net effect of this dynamic and intricate system-level interaction is reflected in the phenotypic presentation of MASLD. Therefore, the application of precision medicine in this scenario aims at complex phenotyping with consequent individual risk prediction, development of individualized preventive strategies, and improvements in the clinical trial designs. In this review, we aim to highlight the importance of precision medicine approaches in MASLD, including the use of novel biomarkers of disease, and its subsequent utilization in future study designs.
Keywords: biomarkers; steatosis; MASLD; cirrhosis; precision medicine